A Nurse-Navigated, Postpartum Support Text Messaging Intervention: Satisfaction Among Primiparous Women. Issue 4 (October 2021) - Morris, Melanie Hall; Barton, Maureen; Zane, Marietta; Hutson, Sadie P.; Raman, Rameela; Heidel, R. Eric
Abstract : More than 50% of maternal deaths in the United States occur during the first year following childbirth. Nearly 40% of these deaths occur between days 1 and 41 of the postpartum period. Historically, women receive less attention from healthcare providers during the postpartum period when compared with the care provided during pregnancy and childbirth. Women may not return for scheduled follow-up care until 4 to 6 weeks after birth, if they return at all. The role of postpartum nurse navigator (PPNN) was developed to deliver a novel, text messaging intervention as part of a randomized controlled trial to 43 primiparous women who experienced an unplanned cesarean birth. Through daily, interactive text messaging, the PPNN assessed study participants' general well-being, assisted with symptom navigation, offered anticipatory guidance, and provided informational support until 4 weeks postpartum. Satisfaction with the intervention was evaluated using a survey that incorporated quantitative and qualitative responses. Overwhelmingly, 93% of participants rated their overall experience with the text messaging intervention as outstanding or good. At least 95% of the participants indicated that they would likely choose to receive daily text messaging from a PPNN following a subsequent birth. Convenient access to professional nurse support for women postbirth warrants further evaluation.